Analysis of the Role of DPS in Assessing the Suitability of Savings Products at BMT - Vina Khoirotun Nisa; Ansori, miswan (LP2M IAIN Palopo, 2024)
This study aims to analyze the role of the Sharia Supervisory Board ( DPS ) in assessing the conformity of savings products at KSPPS Artha Makmur Jaya with sharia principles. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with DPS members, KSPPS BMT management, and other related parties, and supplemented with secondary data from relevant documentation and literature. The results of the study indicate that DPS has a significant role in ensuring the sharia conformity of savings products, with active involvement in the design, evaluation, and monitoring processes of the products. Despite facing challenges such as limited resources and differences in interpretation of sharia principles, DPS has succeeded in carrying out its duties through increased cooperation and a collegial approach in decision-making. The existence of DPS has been proven to increase sharia compliance and member trust in KSPPS Artha Makmur Jaya. The conclusion of this study emphasizes the importance of strengthening the capacity and coordination of DPS to support the development of sustainable sharia finance at KSPPS. K